Slavery, corruption, and institutions - Michael Rauscher; Bianca Willert (Universität Rostock, Institut für Volkswirtschaftslehre, 2019)
We develop a model where firms profit from coercing workers into employment under conditions violating national law and international conventions and where bureaucrats benefit from accepting bribes from detected perpetrators. Firms and bureaucrats are hetero-geneous. Employers differ in their unscrupulousness regarding the use of slave labour whereas bureaucrats have differing intrinsic motivations to behave honestly. Moreover, there is a socially determined warm-glow effect: honest bureaucrats feel better if their colleagues are honest too. The determination of bribes is modelled via Nash bargaining between the firm and the corrupt civil servant. It is shown that multiple equilibria and hysteresis are possible. Depending on history, an economy may be trapped in a locally stable high-corruption, high-slavery equilibrium and major changes in government policies may be necessary to move the economy out of this equilibrium. Moreover, we show that trade bans that are effective in reducing slavery in the export industry tend to raise slavery in the remainder of the economy. It is possible that this leakage effect dominates the reduction of slavery in the export sector.
Keywords: D73; F16; J47; 330; Coerced Labour; Modern Slavery; Corruption; Social Norms; Trade-Related Process Standards